PENGARUH DISIPLIN KERJA, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH PEKALONGAN - Primananda, Natasya; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2015)
The goal of this research is to analyze the impact of work discipline, organizational culture, and work environment to employees performance in Sekretariat daerah Pekalongan. This research uses Work discipline, Organizational Culture, and Work Environment as independent variables , and Employees Performance as dependent variable. The sample in this research was civil servants of Sekretariat Daerah Pekalongan as many as 52 respondents using convenience sampling method. The methods of this reasearch are reliabiity test, validity test, and classical assumption test. The result shows that work discipline, organizational culture, and work environment have impact to employees performance. Based on Adjusted R Square is 0,616 showing that employees performance in Sekretariat Daerah Pekalongan is related with 3 independent variables